Population Genetics of the Cave-dwelling Dusky Fruit Bat, Penthetor lucasi, Based on Four Populations in Malaysia - Mohd Ridwan, A.R; Abdullah, M.T (Universiti Putra Malaysia Press, 2012)
The population genetics of P. lucasi was inferred using 1,061 base pairs (bp) of the Cytochrome b mitochondrial gene. A total of 77 individuals were classified a priori according to their localities, namely, Miri, Kuching, Sri Aman and Kelantan. Results showed that the populations of P. lucasi were separated into two haplogroups, namely, Haplogroup 1 (found in Miri and Kuching populations) and Haplogroup 2 (Miri, Kuching, Sri Aman and Kelantan populations). This separation was supported by bootstrap values in the phylogenetics analyses (94.9% in the maximum likelihood and 100% in Bayesian). A high level of genetic divergence was detected between two haplogroups (3.88%) and this separation could be related to historical events which include multiple colonisation and Pleistocene refugia during the Last Glacial Maximum ice age period. High genetic divergence within Miri (4.93%) and Kuching (4.72%) populations could be due to the presence of a species complex within the P. lucasi populations. The presence of haplotypes from both the populations in Haplogroup 1 and Haplogroup 2 might be due to the ability of this particular species of bats to perform long-distance flight for foraging. A high gene flow between these populations suggests a widespread female gene flow of P. lucasi, judging from the distance of both localities. Meanwhile, the absence of a deep structure from the haplotype trees further proves that P. lucasi may have had wide dispersal ability since the Pleistocene has allowed for genetic exchange to occur between the regions in Malaysia.